A Study Conducted to Find the Usefulness of Sclerotherapy and Band Ligation as Treatment Modalities in Second Degree Internal Haemorrhoids (Medical Forum Monthly, 2024)
Objective: To analyze the efficacy and success rate of sclerotherapy (ST) and rubber band ligation (RBL) for the treatment of second degree internal haemorrhoids.Study Design: Cross-sectional prospective studyPlace and Duration of Study: This study was conducted at the Surgical Units, Civil Hospital Karachi from June 2011 till August 2013.Materials and Methods: Total 130 patients were selected out of 300 with second degree internal haemorrhoids without first, third or secondary haemorrhoids, anal fistula, anal fissures or perianal sinus. They were divided into two equal groups; i.e rubber band ligation (RBL) group and sclerotherapy (ST) group, consisted of 65 patients in each group.Results: The major complaint was of pain 128(98.46%) patients, relieved within 3±days in ST-group & took longer approximately 7±days in RBL-group. Bleeding per rectum was present in 102 (77.69%) patients; out of which 51 patients were treated by RBL 49 (96.08%) got relieve immediately; but two took 2 weeks because of the complication of band slippage and got settled after repeat procedure. Complain of constipation was present in 89(68.46%) patients, 88(98.8%) got relived from the symptom after treatment. Mucus discharge & tenesmus were relieved in both groups after treatment.Conclusion: By ST and RBL second degree haemorrhoids can be treated with good success rate and efficacy in OPD setup. These also unload the economic burden on hospital and patient.